2006
DOI: 10.1590/s0101-20612006000300030
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de diferentes processamentos sobre o teor de ácido ascórbico em suco de laranja utilizado na elaboração de bolo, pudim e geléia

Abstract: RESUMOEste estudo teve por objetivo avaliar a estabilidade do ácido ascórbico em suco de laranja cv. "Pêra" utilizado como ingrediente na elaboração de bolos, pudins e geléia. Os bolos e os pudins foram assados em forno convencional e de microondas, e a geléia foi elaborada em tacho aberto. Estas preparações foram submetidas a análises para determinação dos teores de ácido ascórbico e de sólidos solúveis totais, da acidez total titulável e do pH. Os teores de ácido ascórbico em bolos e pudins, quando comparado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 15 publications
3
8
0
8
Order By: Relevance
“…In this study, Imperial cultivar showed promising results, since its vitamin C content was similar to that found for orange, citrus fruit considered as a reference for vitamin C content (SILVA et al, 2006;. PADAYATTY et al, 2003).…”
Section: Resultssupporting
confidence: 77%
“…In this study, Imperial cultivar showed promising results, since its vitamin C content was similar to that found for orange, citrus fruit considered as a reference for vitamin C content (SILVA et al, 2006;. PADAYATTY et al, 2003).…”
Section: Resultssupporting
confidence: 77%
“…Both unripe and ripe fruit jellies showed higher IC 50 value, which is related to lower antioxidant activity. The reduce in AA content resulting from jelly processing was previously reported by SILVA et al (2006) in jelly made of orange juice, with 75% of retention in ascorbic acid content. Thermal processing can reduce the levels of phytochemicals due to lost of cellular integrity by enzymatic action or by factors such as light and oxygen (VOLDEN et al, 2008).…”
Section: ------------------------Unripe Fruits ----------------------supporting
confidence: 64%
“…Processing cause nutritional changes in foods, but it also makes them more sensorially appealing to the consumers and increases their shelf life (SILVA et al, 2006). Processing can affect the levels of some bioactive compounds of fruits and vegetables due to the exposure to oxygen and long periods of high temperature (RODRIGUEZ-AMAYA, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The persimmon jellies presented values of solids superior to 65 o Brix, in line with this recommendation. SILVA, LOPES and VALENTE-MESQUITA (2006) in the elaboration of orange jelly, found value of 65 ºBrix, value identical to that found by DAMIANI et al (2008), who elaborated a jelly from mango peels. FOLEGATTI et al (2003) still in the study of industrial use of umbu, processed the jelly at the proportions of 40:60 and 50:50 and obtained values of 67.5 ºBrix and 67.1 ºBrix, respectively.…”
Section: Pulp and Jellies Characterizationsupporting
confidence: 77%